Are There Heavyweight Perceptual Reasons? - Ranalli, Chris (International journal for the study of skepticism, 2021)
Genia Schönbaumsfeld has recently argued for the view that our ordinary perceptual reasons provide support for heavyweight metaphysical and epistemological views, such as that there is a mind-independent physical world. Call this the Heavyweight Reasons Thesis. In this paper, I argue that we should reject the Heavyweight Reasons Thesis. I also argue that the rejection of the Heavyweight Reasons Thesis is compatible with the Factive Perceptual Reasons Thesis, the thesis that our perceptual reasons for our ordinary beliefs can be factive, but that factive reasons aren’t necessarily better reasons than subjectively indiscriminable non-factive reasons.